Magnetic Fields and Fragmentation of Filaments in the Hub of California-X - Eun Jung Chung; Chang Won Lee; Woojin Kwon; Mario Tafalla; Shinyoung Kim; Archana Soam; Jungyeon Cho (The Astrophysical Journal, 2023)
We present 850 μ m polarization and C ^18 O (3-2) molecular line observations toward the X-shaped nebula in the California molecular cloud using James Clerk Maxwell Telescope (JCMT)’s SCUBA-2/POL-2 and HARP instruments. The 850 μ m emission shows that the observed region includes two elongated filamentary structures (Fil1 and Fil2) having chains of regularly spaced cores. We measured the mass per unit length of the filaments and found that Fil1 and Fil2 are thermally super- and subcritical, respectively, but both are subcritical if nonthermal turbulence is considered. The mean projected spacings ( ${\rm{Δ }}\bar{S}$ ) of the cores in Fil1 and Fil2 are 0.13 and 0.16 pc, respectively. ${\rm{Δ }}\bar{S}$ is smaller than 4× the filament width expected in the classical cylinder fragmentation model. The large-scale magnetic field orientations shown by Planck are perpendicular to the long axes of Fil1 and Fil2, while those in the filaments obtained from the high-resolution polarization data of JCMT are disturbed, but those in Fil1 tend to have longitudinal orientations. Using the modified Davis–Chandrasekhar–Fermi method, we estimated the magnetic field strengths ( B _pos ) of the filaments, which are 110 ± 80 and 90 ± 60 μ G, respectively. We calculated the gravitational, kinematic, and magnetic energies of the filaments, and found that the fraction of magnetic energy is larger than 60% in both filaments. We propose that the dominant magnetic energy may lead the filament to be fragmented into aligned cores as suggested by Tang et al., and the shorter core spacing can be due to a projection effect via the inclined geometry of the filaments or due to nonnegligible longitudinal magnetic fields in the case of Fil1.